1997
DOI: 10.1016/s0194-5998(97)70121-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Racial Variations in Cephalometric Analysis

Abstract: Cephalometric analysis has earned a vital role in the evaluation of obstructive sleep apnea. However, the normal measurements cited in the literature are not sex or race specific. Skeletal differences in sexes and races have been established. This study was initiated to examine whether race and sex variations in soft tissue and skeletal measurements exist in cephalometric analysis. A total of 89 volunteers of different race and sex participated in this study. The data support the hypothesis that there are stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 3 publications
1
55
0
4
Order By: Relevance
“…25 In addition, a recent study showed that gender and racial variations are present in cephalometric parameters. 26 Because the structural relationship between the hard and soft tissues of the upper airway is confounded by obesity, which independently remains an important factor for increasing apneic activity, it is important to know which craniofacial parameters are risk factors for nonobese young adults. For Asian men, a BMI exceeding 27 kg/m 2 is defined as being obese.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, a recent study showed that gender and racial variations are present in cephalometric parameters. 26 Because the structural relationship between the hard and soft tissues of the upper airway is confounded by obesity, which independently remains an important factor for increasing apneic activity, it is important to know which craniofacial parameters are risk factors for nonobese young adults. For Asian men, a BMI exceeding 27 kg/m 2 is defined as being obese.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences influenced by sex are also noticed. OSA in males is connected with visceral obesity, whereas in females, it concerns general adiposity [9].…”
Section: Introductionmentioning
confidence: 99%
“…A number of factors have been postulated to be involved in causing these differences. These include hormonal effects, anatomical influences, and differences in the mechanics of the upper airway and in the control of breathing [3,[7][8][9][10][11][12]. Given the myriad dissimilarities in the two genders with regards to the mechanisms and manifestations of OSA, we hypothesize that men and women will differ with regards to the positive airway pressure requirements for treatment of OSA.…”
Section: Introductionmentioning
confidence: 99%